Performance of Bali Cattle by the Implementation of Quadruple Helix Participatory-Based Breeding Programs in Optimizing the Potential of Smallholder Cattle Farms - Zulkharnaim, Zulkharnaim; Baba, Syahdar; Hatta, Muhammad; Ali, Hikmah M. (Universitas Sebelas Maret, 2024)
Objective: This study aims to determine the impact of implementing a participatory-based breeding program on productivity as represented by cattle morphometric measures, technical coefficients and supporting factors among smallholder farmers in Barru District, South Sulawesi Province. Methods: The research method used 1,040 cattle recordings from 2017 to 2022 in Barru district, South Sulawesi Province, Indonesia, with the following sub-districts being included: Tanete Riaja, Tanete Rilau, Balusu, Barru, and Mallusetasi. The study employed descriptive analysis, a paired-sample T test, and an analysis of the interaction between breeding variables using the general linear model. Results: The results showed that the morphometric size of participatory-based breeding programs (PBBP) had higher CG values (p<0.01) than non-participatory breeding programs (NPBBP).. The NI PBBP value was found to be in the low category (33.82%), while the NPBBP value was found to be 6.94%. A further impact was observed, whereby male and female calves exhibited distinct differences in WH, BL and CG each year between 2020-2022, with statistical significance (p<0.01). Conclusions: This study showed that factor breeding program models (PBBP and NPBBP) significantly influenced the morphometric size (p < 0.01). The implementation of the PBBP scheme has had a positive impact, as evidenced by the application of the Quadruple Helix model.